2014
DOI: 10.4103/1658-354x.140817
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of altered hemodynamics after spinal anesthesia: A comparison of volume preloading with tetrastarch, succinylated gelatin and ringer lactate solution for the patients undergoing lower segment caesarean section

Abstract: Background:Spinal anesthesia has replaced general anesthesia in obstetric practice. Hemodynamic instability is a common, but preventable complication of spinal anesthesia. Preloading the circulation with intravenous fluids is considered a safe and effective method of preventing hypotension following spinal anesthesia. We had conducted a study to compare the hemodynamic stability after volume preloading with either Ringer's lactate (RL) or tetrastarch hydroxyethyl starch (HES) or succinylated gelatin (SG) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Only two studies reported the requirement of phenylephrine following spinal anesthesia induced hypotension. [ 39 , 44 ] A statistically significant reduction in phenylephrine requirement was observed with the use of colloid preloading compared with crystalloid preloading (standardized mean difference: -0.54, 95% CI: -0.82 to -0.25; 169 women; I 2 = 0%, P = .0002).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Only two studies reported the requirement of phenylephrine following spinal anesthesia induced hypotension. [ 39 , 44 ] A statistically significant reduction in phenylephrine requirement was observed with the use of colloid preloading compared with crystalloid preloading (standardized mean difference: -0.54, 95% CI: -0.82 to -0.25; 169 women; I 2 = 0%, P = .0002).…”
Section: Resultsmentioning
confidence: 98%
“…The incidence of intraoperative nausea and/or vomiting was reported in 20 trials. [ 15 , 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 , 32 35 , 37 , 39 – 42 , 44 , 47 ] Among these trials, a statistically significant reduction in nausea and/or vomiting was found when colloid preloading was administered compared with crystalloid preloading (risk ratio: 0.72, 95% CI: 0.55–0.95; 1601 women; P = .02; Fig. 5 ) with mild heterogeneity ( I 2 = 36%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten articles listed below,[ 1 2 3 4 5 6 7 8 9 10 ] all with the same corresponding author and published in the Saudi Journal of Anaesthesia from 2014-2018, are being retracted because they have been found to have a number of unattributed sections of content with high rate of similarity from various other articles along with overwhelming evidence of data fabrication. The corresponding author and his institution were contacted and asked to provide the journal with the raw data for these studies but there has been no adequate response within a reasonable timeframe.…”
mentioning
confidence: 99%